Sealed Bid Auctions vs. Ascending Bid Auctions: An Experimental Study - Christer Andersson; Ola Andersson; Tommy Andersson (Research Institute of Industrial Economics (IFN), 2011)
This paper considers the sealed bid and ascending auction, which both identifies the minimum Walrasian equilibrium prices and where truthful preference revelation constitutes an equilibrium. Even though these auction formats share many theortical properties, there are behavioral aspects that are not easily captured. To explore this issue in more detail, this paper experimentally investigates what role the design of the auction format has for its outcome. The results suggest that the sealed bid mechanism performs weakly better in all of investigated measures (consistent reporting, efficiency etc.). In addition, we find that the performance of the ascending auction is increasing over time, whereas the sealed bid auction shows no such tendency.
Keywords: C91; D44; 330; Auctions; Non-manipulability; Efficiency; Experiments; Auktionstheorie; Mechanismus-Design-Theorie; Manipulation; Test